Hubungan antara Status Sosial Ekonomi Orang Tua dengan Minat Siswa Melanjutkan Studi Ke Perguruan Tinggi pada Siswa Kelas XII SMA Negeri 2 Lengayang - Eldariani, Rahmi; Ananda, Azwar (ANWARUL, 2025)
This study aims to examine the relationship between parents' socioeconomic status and students' interest in pursuing higher education among XII-grade students at SMA Negeri 2 Lengayang. The research was motivated by the low percentage of students from SMA Negeri 2 Lengayang who continue their studies at the university level. This study employs a quantitative method with a correlational approach. The sampling technique used is purposive sampling, with a total sample of 80 XII-grade students. Data were collected using a Likert scale questionnaire consisting of 15 statements that had been tested for validity and reliability. The results indicate a significant positive relationship between parents' socioeconomic status and students' interest in higher education, as shown by the calculated correlation coefficient (r = 0.454), which is greater than the critical r-value (r = 0.220). Consequently, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. Based on these findings, it can be concluded that the higher the parents' socioeconomic status, the greater the students' interest in continuing their education at the university level.